Simple and efficient protocol to isolate and culture brain microvascular endothelial cells from newborn mice - Nicolicht-Amorim, Priscila; Delgado-Garcia, Lina M.; Nakamura, Thabatta Karollynne Estevam; Courbassier, Natália Rodrigues; Mosini, Amanda Cristina; Porcionatto, Marimelia A. (Frontiers in Cellular Neuroscience, 2022)
The neurovascular unit (NVU) is a multicellular structure comprised of neurons, glial cells (astrocytes and oligodendrocytes), and non-neural cells (brain microvascular endothelial cells or BMECs, pericytes, smooth muscle cells, and microglia), and it is supported by the basal lamina, a specialized extracellular matrix. BMECs have a mesodermal origin and invade the nervous system in the early stages of neural tube development, forming the blood-brain barrier's (BBB) anatomical core. BMECs are connected by adherent junction complexes composed of integral membrane and cytoplasmic proteins. In vivo and in vitro studies have shown that, given the proximity and relationship with neural cells, BMECs acquire a unique gene expression profile, proteome, and specific mechanical and physical properties compared to endothelial cells from the general vasculature population. Hence those cells are fundamental in maintaining brain homeostasis by regulating transcellular and paracellular transport of fluids, molecules, and cells. Therefore, it is essential to gain in-depth knowledge of the dynamic cellular structure of the cells in the NVU and their interactions in health and disease. Here we describe a simplified protocol using C57BL/6 newborn mice at postnatal day 1 (PND1) to isolate, purify, and culture BMECs monolayers in two different substrates (coverslips and inserts). Finally, we tested BMECs function using an oxygen-glucose deprivation (OGD) model. In vitro characterization and validation of the primary culture of BMECs monolayers seeded in plastic and insert included light microscopy during the culture period, immunolabeling, and gene expression profile. Transendothelial electrical resistance (TEER) measurement was used as a functional assay of the adherent junction complexes. The protocol presented here for the isolation and culture of BMECs is more straightforward than previously published protocols, yields a high number of purified cells, and may be suitable for the use as bioscaffold for secondary cell seeding allowing the study and better understanding of the NVU.